The Effect of Service Quality on Customer Satisfaction Using Goods Delivery Services in Makassar City - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Fundamental and Applied Management Journal, 2023)
This study aims to determine whether the dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy affect customer satisfaction of Goods Delivery Services in Makassar City and analyze the most dominant factors in influencing customer satisfaction of Goods Delivery Services in Makassar City. The population in this study were all customers at the Goods Delivery Service in Makassar City, totaling 8544. The sample taken was 100 respondents using Non-Probability Sampling technique with Purposive sampling approach. The results showed that all independent variables each had a positive and significant effect on the dependent variable. Simultaneously all service quality variables have a positive and significant influence on customer satisfaction. Goods Delivery Services in Makassar City need to maintain elements that have been rated well by customers such as empathy, tangible, and responsiveness, on the other hand, they need to improve things that are still lacking, namely assurance.